2020
DOI: 10.1186/s12884-020-2808-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the adolescent pregnancy rate in Thailand 2008–2013: an application of capture-recapture method

Abstract: Background: Adolescent pregnancy is an important health and social issue that affects both individual and social well-being. However, deriving a national estimate is challenging in a country with multiple incomplete national databases especially the abortion statistics. The objective of this study was to estimate the adolescent pregnancy rates in Thailand using capture-recapture method. Methods: An application of capture-recapture method was conducted using two cross-sectional databases (i.e., the national bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The Department of Health's goal for 2026 is for the live birth rate for girls aged 10-14 years not exceeding 0.5 per 1,000. 4 In Chiang Mai, a province of northern Thailand, the report in 2021 showed that the birth rate among pregnant adolescents aged 10-14 increased from 1.3 per 1,000 in 2020 to 1.6 per 1,000, 8 which is higher than the countrywide level. With increasing sexual activity occurring in primary school, there is a need to provide comprehensive sexuality education to these children.…”
Section: Pacific Rim Int J Nurs Res • January-march 2024mentioning
confidence: 99%
See 1 more Smart Citation
“…The Department of Health's goal for 2026 is for the live birth rate for girls aged 10-14 years not exceeding 0.5 per 1,000. 4 In Chiang Mai, a province of northern Thailand, the report in 2021 showed that the birth rate among pregnant adolescents aged 10-14 increased from 1.3 per 1,000 in 2020 to 1.6 per 1,000, 8 which is higher than the countrywide level. With increasing sexual activity occurring in primary school, there is a need to provide comprehensive sexuality education to these children.…”
Section: Pacific Rim Int J Nurs Res • January-march 2024mentioning
confidence: 99%
“…7 Furthermore, the adolescent pregnancy rate in Thailand has become the second highest in Southeast Asia. 8 Over 50 out of every 1000 girls aged 15 to 19 give birth yearly. 4 Adolescent birth rate for girls aged 10-14 years in 2022 decreased from 0.9 per 1,000 in 2021 to 0.8 per 1,000, but it remains higher than the Department of Health's goal.…”
Section: Pacific Rim Int J Nurs Res • January-march 2024mentioning
confidence: 99%
“…Therefore, an appropriate contraceptive service is needed for all adolescents [ 10 ]. The problem of adolescent pregnancy is of concern in Thailand [ 11 ], and so the Thai government launched the adolescent pregnancy prevention program in 2014. This program aimed to increase effective contraception for adolescents by offering no cost LARC for Thai women aged under 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…8 Moreover, it has been observed through the evidence that the this number of adolescent pregnancy is more in the southern part of Thailand including Chumpon province, Krabi province, and Nakhon Si Thammarat province. 9 This problem of adolescent pregnancy has not yet been resolved. Moreover, proper information and knowledge for adolescents on sexual health literacy, early aged pregnancy, sexually transmitted diseases (STD), childbearing information and care are highly needed.…”
Section: Introductionmentioning
confidence: 99%